Exploiting Nanomaterial‐Mediated Autophagy for Cancer Therapy. Issue 2 (15th November 2018) - Wei, Weijun; Rosenkrans, Zachary T.; Luo, Quan‐Yong; Lan, Xiaoli; Cai, Weibo
Abstract: Autophagy is a conserved process that is critical for sequestering and degrading proteins, damaged or aged organelles, and for maintaining cellular homeostasis under stress conditions. Despite its dichotomous role in health and diseases, autophagy usually promotes growth and progression of advanced cancers. In this context, clinical trials using chloroquine and hydroxychloroquine as autophagy inhibitors have suggested that autophagy inhibition is a promising approach for treating advanced malignancies and/or overcoming drug resistance of small molecule therapeutics (i.e., chemotherapy and molecularly targeted therapy). Efficient delivery of autophagy inhibitors may further enhance the therapeutic effect, reduce systemic toxicity, and prevent drug resistance. As such, nanocarrier‐based drug delivery systems have several distinct advantages over free autophagy inhibitors that include increased circulation of the drugs, reduced off‐target systemic toxicity, increased drug delivery efficiency, and increased solubility and stability of the encapsulated drugs. With their versatile drug encapsulation and surface‐functionalization capabilities, nanocarriers can be engineered to deliver autophagy inhibitors to tumor sites in a context‐specific and/or tissue‐specific manner. This review focuses on the role of nanomaterials utilizing autophagy inhibitors for cancer therapy, with a focus on their applications in different cancer types. Abstract : Autophagy is a conserved process that is critical for sequestering and degrading proteins, damaged or aged organelles, and for capturing nanoparticles . Clinical trials have suggested that autophagy inhibition is a promising approach for treating advanced malignancies. With their versatile drug encapsulation and surface‐functionalization capabilities, nanocarrier‐based delivering of autophagy inhibitors has several distinct advantages over free autophagy inhibitors.